Numerical simulation of the combustion process of a pellet-drop-feed boiler. (15th November 2016) - Gómez, M.A.; Porteiro, J.; de la Cuesta, D.; Patiño, D.; Míguez, J.L.
Highlights: A 3D transient model for fixed bed combustion was applied in a biomass boiler. The thermal conversion of solid wood was modelled by a group of transport equations. Two different feeding regimes were introduced to study the bed dynamics. The models were applied to a real boiler to analyze its overall behavior. Abstract: This paper presents a transient model for the simulation of biomass combustion in a fixed bed boiler fed through particle drop. The method combines classical CFD techniques, which are used to simulate the gas phase, with a set of Eulerian variables defined to model the solid phase and Lagrangian trajectories that model the particle drop. Several submodels are implemented to simulate the numerous processes that occur during the combustion of the solid phase. These submodels include the thermal conversion of biomass, heat and mass transfer, particle shrinkage and bed compaction as well as the interaction of the DPM (Discrete Phase Model) trajectories and the bed variables. The predictions are contrasted with various experimental tests, which provide reasonably good results and demonstrate the overall good behavior of the models. The simulation facilitates an understanding of the heat transfer inside the boiler and the instability of the emission measurements.